Cultivating American- and Japanese-Style Relatedness Through Mother–Child Conversation. Issue 4 (19th May 2017) - Crane, Lauren Shapiro; Fernald, Anne
Abstract : This study investigated whether European American and Japanese mothers' speech to preschoolers contained exchange- and alignment-oriented structures that reflect and possibly support culture-specific models of self-other relatedness. In each country 12 mothers were observed in free play with their 3-year-olds. Maternal speech was coded for linguistic framing and frame-function mapping, using a cross-linguistically informed coding scheme rooted in aspects of English and Japanese grammar. American and Japanese mothers were remarkably similar in the number of queries, declaratives, and imperatives they produced. At the same time, Americans tended to verbally frame the mother–child relationship in terms of idea exchange between allies with individual perspectives, whereas Japanese tended to frame it in terms of mutually shared points of view. These significant findings are consistent with the idea of independent and interdependent self-schemas in the United States and Japan and suggest that language socialization might contribute to the development of American- and Japanese-style relatedness models.